UV-Fast: Development of spaces for large-scale sterilization by ultraviolet-C (UV-C) irradiation of personal protective equipment (PPE) in hospitals for their reuse - Zille, Andrea (2021)
UV-Fast: Development of spaces for large-scale sterilization by ultraviolet-C (UV-C) irradiation of personal protective equipment (PPE) in hospitals for their reuse Desenvolvimento de espaços para a esterilização por irradiação ultravioleta-C (UV-C) em larga escala de Equipamentos de Proteção Individual (EPIs) nos hospitais para a sua reutilização FCT Project Research4Covid-19 Reference: 011_595803006